Profil Kapasitas Volume Oksigen Maksimal Mahasiswa Pendidikan Guru MI UIN Sunan Gunung Djati Bandung - Rahman, Alvin Yanuar; Putra, Andhika Yahya; Putra, Roy Try (Wahana Pendidikan, 2023)
The purpose of this study was to determine the VO2 Max capacity of the students of PGMI FTK UIN Sunan Gunung Djati Bandung. The research method uses descriptive qualitative research in the form of using a test survey method. The measurement test uses a multi-stage test or Multi Stage Fitness Test (MFT). Data were analyzed using percentages. The research sample was 435 students of PGMI FTK UIN Sunan Gunung Djati Bandung. Based on data on the frequency of VO2 Max capacity, students of PGMI FTK UIN Sunan Gunung Djati Bandung 0.68% are in the medium category, 75.86% are in the less category, and 23.44% are in the very poor category. Based on the results, the largest percentage of the VO2 Max capacity of the students of PGMI FTK UIN Sunan Gunung Djati Bandung was mostly in the less category.